Perceptions of water access in the context of climate change by rural households in the Seke and Murewa districts, Zimbabwe - Shakespear Mudombi; Mammo Muchie (Jàmbá, 2013)
The objective of the study was to assess perceptions of rural household heads with regard to various aspects of water access and climate change, and to evaluate whether there were significant differences in perceptions of respondents from female-headed and male-headed households. The study is based on a cross-sectional survey of 300 respondents conducted in the Seke and Murewa districts of Zimbabwe in 2011. The analysis included mainly descriptive statistics. The majority of both female-headed and male-headed households relied on rainfall for their crops, rivers were cited as the main water source for their livestock and protected wells supplied water for household use. Households experienced water shortages, which were attributed mainly to reduced rainfall. The general perception was that there would be less water available in future, with a greater proportion of female-headed than male-headed households perceiving such difficulties. However, very few respondents indicated that they would consider emigrating, although female-headed households were more likely to consider emigrating than male-headed households. A considerable number of respondents indicated that they did not have any means to overcome the water shortages. This highlights the need for interventions such as training and empowerment of individuals with regard to sustainable water use and management.